Corrigendum to “Ventilation provision and use in homes in Great Britain: A national survey” [Build. Environ. 27 (2024) 111528] - Cairan Van Rooyen; Tim Sharpe (Building and Environment, 2024)

Ventilation provision and use in homes in Great Britain: A national survey - Cairan Van Rooyen; Tim Sharpe (Building and Environment, 2024)

Environmental data monitoring and infection risks in UK care-homes in the context of COVID-19 - Kishwer Abdul Khaliq; Sara Mohamad; Alexander J. Edwards; Catherine Noakes; Andrew H. Kemp; Carl Thompson; Gráinne McGill; Tim Sharpe (Building and Environment, 2024)

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.